Constraining mass variations in the Siberian permafrost region based on GRACE and Satellite Altimetry - Shabanloui, Akbar; Müller, Jürgen (My University, 2014)
The permafrost layers in the Siberia (Russia) with different thicknesses cover about 80% of this region. Therefore these frozen sheets play an important role for the hydrological water cycle of the Earth system. The integral mass variations in the Earth system with different spatial-temporal resolution are determined based on GRACE observations/products. On the one hand, the mass variations in this region are precisely estimated based on the new release of GRACE Level 2 products from GFZ (RL05a). On the other hand, these (hydrological) mass variations can be geometrically determined based on satellite (radar/laser) altimetry tracking data. The mass variations in this region are extracted from lake (see) level variations that observed by satellite altimetry missions (e.g. Jason-2, ICESat). In this investigation, the mass variations in the Siberian region that concluded from satellite altimetry missions are used to constrain hydrological mass variations from GRACE mission. This sort of constraining results should present a realistic mass transport pattern.